Türkiye'de Somut Olmayan Kültürel Mirasın Medyaya Yansıması ve Kültür Endüstrisi Sorunu. - KILINÇ, Elif Pınar (Journal of Selcuk University Social Sciences Institute / Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
The question of whether the use of the media, which is functional in the culture industry dominated by capitalist relations, for the protection and preservation of the elements identified in the 2003 UNESCO Convention on the Safeguarding of Intangible Cultural Heritage is a threat or an opportunity constitutes the problem of the article. The study aims to reveal the stage reached by the controversial situation of the media and its function in today's digital media. The data is analyzed by adopting a historical approach through literature and document analysis and evaluated through examples. The data on the frequency of the cultural elements on the list in Hürriyet, Sabah, Milliyet, Sözcü, Posta, Haber Türk and Yeni Şafak newspapers, which are respectively the most viewed newspapers in Turkey, were obtained by scanning with the web scraping technique using the Python programming language. The most important finding that emerged is that beyond the fact that the media poses a risk or opportunity for the protection of cultural heritage, this heritage does not find enough space in digital media; and when it does, it is dominated by an understanding that lacks the planning, sensitivity and care required for its protection and preservation.